Fluids of the Future - Edwards, Thomas H.; Hoareau, Guillaume L. (Frontiers in Veterinary Science, 2021)
Fluids are a vital tool in the armament of acute care clinicians in both civilian and military resuscitation. We now better understand complications from inappropriate resuscitation with currently available fluids; however, fluid resuscitation undeniably remains a life-saving intervention. Military research has driven the most significant advances in the field of fluid resuscitation and is currently leading the search for the fluids of the future. The veterinary community, much like our civilian human counterparts, should expect the fluid of the future to be the fruit of military research. The fluids of the future not only are expected to improve patient outcomes but also be field-expedient. Those fluids should be compatible with military theaters or natural disaster environments. For decades, military personnel and disaster responders have faced the peculiar demands of austere environments, prolonged field care, and delayed evacuation. Large scale natural disasters present field limitations often similar to those encountered in military theaters. The fluids of the future should, therefore, have a long shelf-life, a small footprint, and be resistant to large temperature swings, for instance. Traumatic brain injury and hemorrhagic shock are the leading causes of preventable death for military casualties. Strong of this knowledge, the military health system is focusing efforts on field-expedient fluids that will be specifically relevant for the management of those conditions. Fluids are expected to be compatible with blood products, increase oxygen-carrying capabilities, promote hemostasis, and be easy to administer in the prehospital setting, to match the broad spectrum of current acute care challenges, such as sepsis and severe systemic inflammation. This article will review historical military contributions to current resuscitation strategies, describe the expectations for the fluids of the future, and describe select ongoing research efforts with a review of current animal data.